2017
DOI: 10.24190/issn2564-615x/2017/02.03
|View full text |Cite
|
Sign up to set email alerts
|

Epilobium angustifolium L.: A medicinal plant with therapeutic properties

Abstract: Epilobium angustifolium L. is a medicinal plant belonging to the Onagraceae family, which includes more than 200 different species from all over the world. Traditional medicinal applications include treatment of prostate, gastrointestinal, menstrual disorders and recently it has been used for its analgesic and anti-inflammatory activity. In this investigation E. angustifolium was collected in Ternopil region of Ukraine.The obtained data demonstrated that E. angustifolium herb extract, rich in polyphenolic comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…[4][5][6] WH also shows bioactive properties, such as strong antioxidant activities. [6][7][8][9][10] WH also has properties such as the ability to inhibit the proliferation of cancer cells and antimicrobial properties, [11][12][13] while not being toxic. 14,15 Also, the European Medicines Agency in its 2016 report confirms the lack of side effects of this plant.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] WH also shows bioactive properties, such as strong antioxidant activities. [6][7][8][9][10] WH also has properties such as the ability to inhibit the proliferation of cancer cells and antimicrobial properties, [11][12][13] while not being toxic. 14,15 Also, the European Medicines Agency in its 2016 report confirms the lack of side effects of this plant.…”
Section: Introductionmentioning
confidence: 99%
“…Cumulative evidence has indicated that oenothein B can stimulate the ROS production and trigger apoptosis in a caspase-independent manner [24][25][26]. Cytotoxic and apoptotic effects of E. angustifolium ethanolic extract were investigated and confirmed by MTT and Comet assays [27]. Extracts at concentration of 50-75 µg/ml reduced cell viability and induced DNA damages in hepatocellular carcinoma.…”
Section: Antiproliferative and Cytotoxic Activitiesmentioning
confidence: 99%
“…Other well-known and well-described plants of this family include Epilobium hirsutum L. and Epilobium parviflorum Schreb. [ 2 ]. Fireweed is a plant with a circumpolar range.…”
Section: Introductionmentioning
confidence: 99%